2012
DOI: 10.2320/matertrans.m2011377
|View full text |Cite
|
Sign up to set email alerts
|

Hardness and Wear Properties of Al&ndash;4.5%Cu/Al<sub>3</sub>Mg<sub>2</sub> Nanocomposite Prepared by Mechanical Alloying

Abstract: AlMg alloys close to ¢-Al 3 Mg 2 intermetallic phase were processed by neutral gas coverage melting process of pure elemental Al and Mg with the composition of Al40 mass% Mg. Mechanical milling was applied in order to convert the pre-alloyed ingots to nanocrystalline or amorphous alloy. X-ray diffraction and transmission electron microscopy (TEM) tests were carried out to investigate the formation of Al 3 Mg 2 single phase nanoparticle. Having prepared the single phase intermetallic, it was added to the pre-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…It contains 102 atoms in its monoclinic crystal structure unit, and owes its superior properties to the large number of atoms in its crystal unit. 20,27) The single-crystal growth of a large structure of Al 13 Fe 4 CMA is previously reported. 27) Plastic deformation and interfacial properties of Al-Al 13 Fe 4 have been discussed for an in-situ composite consisting of Al matrix and Al 13 Fe 4 particles.…”
Section: )mentioning
confidence: 93%
See 4 more Smart Citations
“…It contains 102 atoms in its monoclinic crystal structure unit, and owes its superior properties to the large number of atoms in its crystal unit. 20,27) The single-crystal growth of a large structure of Al 13 Fe 4 CMA is previously reported. 27) Plastic deformation and interfacial properties of Al-Al 13 Fe 4 have been discussed for an in-situ composite consisting of Al matrix and Al 13 Fe 4 particles.…”
Section: )mentioning
confidence: 93%
“…20,27) The single-crystal growth of a large structure of Al 13 Fe 4 CMA is previously reported. 27) Plastic deformation and interfacial properties of Al-Al 13 Fe 4 have been discussed for an in-situ composite consisting of Al matrix and Al 13 Fe 4 particles. 13,14,28) Also, it has been shown that Al 13 Fe 4 exhibits a high hardness of 815 HV, a density of 3.8 g/cm 3 , and an estimated surface energy of 2.04 J/m 2 .…”
Section: )mentioning
confidence: 93%
See 3 more Smart Citations